MANAJEMEN MUTU PENDIDIKAN DALAM MENGHADAPI KREATIVITAS ANAK - Syahril Chaniago (Jurnal Ilmiah Econosains, 2012)
ABSTRACTMany people in society are not satisfied with the quality of education in our country. Obviously we often hear phrases like, "our country hasnâ€™t had good quality of education yet", "development of education in Indonesia is very slow and left behind from other countries", "when are we going to make progress if our education system is still running in placeâ€. Therefore, the most important thing to think about is to produce intelligent and competitive human beings.Keywords : Management of Quality Education, Intelligent, and creativity.